RELATIONSHIP BETWEEN VALUES OWNED BY TEACHER CANDIDATES AND THEIR DEMOCRATIC ATTITUDES - Hakan DÜNDAR (Fırat University, 2019)
The objective of this study is to determine the relationship between teacher candidates’ values and their democratic attitudes. The working group involves 164 candidate teachers from senior class of Kırıkkale University Primary Education Department Classroom Teaching program. This is a descriptive research utilizing relational survey model. “Schwartz’ Value Survey” developed by Schwartz (1992) and applied in many countries and many different cultures was used to determine teacher candidates’ values and “Democratic Attitudes Scale” developed by Gözütok (1995) applied in many countries and different cultures was used to determine their democratic attitudes. At the end of the study statistically meaningful relations determined between teacher candidates’ values and their democratic attitudes. After investigating teacher candidates’ values, it was found out that values to which they attached importance mostly is in benevolence dimension and value dimension to which they attached importance at the very least is in power value dimension. It was determined that the teacher candidates have meaningful relations between their hedonism, stimulation, self-direction, benevolence, tradition, conformity, security and universalism values and their democratic attitudes. No statistically meaningful relation was found between achievement and power values and democratic attitudes of teacher candidates. Based on the results of this study; it can be searched how values are perceived by teachers, mainly by teacher candidates. In the meanwhile contents of different and similar aspects of factors affecting values and democratic attitudes of teacher candidates and teachers and their level of effecting can also be investigated. Also qualitative studies can be conducted on the role of the formation of the democratic attitudes and studies relevant to meaningful relation groups given in the results of these studies and value groups where no meaningful relation is found and their reasons.